Ambiguity of Visual Design and Meaning in TV's Battlestar Galactica. - Roth, Lane (Extrapolation (Kent State University Press))
Comments on the ambiguity of visual design and meaning in the science fiction television series "Battlestar Galactica". Presentation of the conflict between man and machine; Design of spaceships; Exterior design; Use of visual motifs that betrays similarities between human and mechanical foes.